Study of dynamics of two-phase flow through a minichannel by means of recurrences. (15th May 2017) - Litak, Grzegorz; Górski, Grzegorz; Mosdorf, Romuald; Rysak, Andrzej
Abstract: By changing air and water flow rates in the two-phase (air–water) flow through a minichannel, we observed the evolution of air bubbles and slugs patterns. This spatiotemporal behaviour was identified qualitatively by using a digital camera. Simultaneously, we provided a detailed analysis of these phenomena by using the corresponding sequences of light transmission time series recorded with a laser-phototransistor sensor. To distinguish particular patterns, we used recurrence plots and recurrence quantification analysis. Finally, we showed that the maxima of various recurrence quantificators obtained from the laser time series could follow the bubble and slugs patterns in studied ranges of air and water flows. Abstract : Highlights: Mixture flows of air and water with changing water and air rates were studied. The character of two-phase flow dynamics were studied by recurrences of the laser light transmissivity time series. Recurrence Quantification Analysis enabled to classify the flow patterns.